COVID-19 Infection Impact on Perceptions Change and Health Protocols Compliance in Survivors - Nazila Tanasya; Dewi Santosaningsih; Nanik Setijowati (Jurnal Ilmu Kedokteran Keluarga, 2023)
Increasing cases of COVID-19 infection in Indonesia have prompted the Indonesian Ministry of Health to establish health protocols to prevent COVID-19. According to Satuan Tugas Penanganan COVID-19, the increase in cases in July-August 2021 was caused by 9.5% of not wearing masks behavior and 11.2% of not keeping a distance and avoiding crowds. This research aimed to determine perceptions of change and health protocol compliance in COVID-19 survivors. The term perceptions in this research were based on the Health Belief Model theory, particularly perceptions of susceptibility, severity, barriers, and benefits. The research design was analytic observational research using a cross-sectional method. The data was collected by distributing questionnaires on Google Forms via online media. The number of respondents is 103 respondents who live in Malang City. This research utilized the Mc Nemar test to examine perceptions change and health protocols compliance on respondents using a 95% degree of confidence, α = 0.05, significant if p < 0.05. The results showed no significant change in survivors' perceptions with p 0.125, and increased compliance by survivors to health protocols with p <0.001. In conclusion, this research examined that the survivors’ perceptions insignificantly changed before and after suffering from Covid-19, and survivors' health protocol compliance significantly increased before and after suffering from Covid-19.